Heredity - Heredity (Springer Nature, 2026)
Heredity publishes novel, insightful papers in all areas of genetics. We publish original research Articles using theoretical, computational, and empirical methods, Computer Notes describing software packages for genetic analyses, and syntheses in the forms of Review Articles, Comments, and Perspectives. We also welcome proposals for special issues and curated collections.
FI 0.92
Q2
Keywords: Life Sciences; Genetics; Ciencias de la vida; Genética; Acuerdos transformativos; Transformative agreements; Genética de poblaciones; Arquitectura del genoma; Citogenética